Respon Pertumbuhan Tanaman Krisan Fase Vegetative Dengan Sistem Penyiraman Otomatis Berbasis Arduino (Sensor Kelembaban Tanah)) - efendi, muhammad rizky; Naim, Abu (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
This study aims to examine the survival and growth of chrysanthemum plants on Arduino-based automatic watering. The procedure of this research included making the ardiuno uno automatic watering device, planting potted chrysanthemum, testing the tool and collecting data on the growth and humidity of potted chrysanthemum. The experiment consisted of 2 treatments, namely watering using an Arduino software based on a humidity sensor and manual watering. The plant varieties used in this study were yellow standard chrysanthemum, red standard chrysanthemum and white standard chrysanthemum. After the plants were 2 weeks after planting (MST), vegetative growth was measured once a week for 7 weeks. Survival analysis was carried out by calculating the percentage of live and dead individual watering results. Growth analysis was performed by multivariete cluster analysis and bioplots using the paleontological statistics (PAST) program. The results of the calculation of the survival percentage show that the watering that has the best survival is arduino uno(DA) watering with 83% and the survival from manual watering (KO) is 80%. The results of the adaptation similarity analysis based on growth characteristics can be grouped into 2 parts. The first group with adaptive characters were DA-SP, KO-SP, KO-SK and DA-SK. The second group with more adaptive characters were DA-SM and KO-SM.